La investigacion social cualitativa en Mexico - Cisneros Puebla, Cesar A. (2005)
Grand interest about interpretative methodology has increased in the last decade Medicine Sociology and Social Psychology are disciplines wiyh noticable influence. Like other countries of Latin America, in Mexico all areas of scientific action are not professionalized completely, Qualitative Social Research in Mexico is changing from participatory observation and participatory action research to interpretative ethnography and Grounded Theory. Health and body, identity and space are themes of raides relevance and are studied with computer assisted analysis